2020
DOI: 10.1021/acs.cgd.0c00617
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Large Single Crystals of n-Type SnS from Halogen-Added Sn Flux

Abstract: We report the growth of large Cl-doped and Brdoped SnS single crystals from a molten Sn-based flux. Compared with the small and lamellar undoped SnS crystals, the addition of SnCl 2 or SnBr 2 halogen sources in the flux substantially enhanced lateral growth along the (100)-plane and vertical growth. The maximum size of the obtained single crystals reached a diameter and thickness of 16 mm and 0.7 mm for the Cl-doped SnS and 24 mm and 1.0 mm for the Br-doped SnS, respectively. The X-ray rocking curves and the X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 55%
See 3 more Smart Citations
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 55%
“…Hall measurements confirmed that the obtained SnS films exhibited p‐type conduction, which is similar to that of the previously reported undoped SnS thin films. [ 25 ] The conductivity, carrier concentration, and Hall mobility of a typical SnS thin film, as well as those of the n‐type SnS single crystal [ 22 ] used as the substrate for the deposition of the p‐type thin film, are shown in Table 1 . The Hall mobility of the p‐type thin film was of the same order of magnitude as the reported values of the undoped SnS thin films (1–4 cm V −1 s −1 ), which were also prepared by radio frequency (RF)‐magnetron sputtering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, two strategies are adopted to realize the ntype conduction in SnS, including cation (Pb 2+ , Sb 3+ , Bi 3+ ) [95][96][97] substitution in Sn sites and halogen anion (Cl − , Br − ) [50,98,99] doping at S sites. The carrier concentration, however, is too low to achieve a good electrical conductivity.…”
Section: Explorations Of N-type Snsmentioning
confidence: 99%